IN VITRO COMPARATIVE EFFICACY OF CIPROFLOXACIN AND CO- TRIMOXAZOLE AGAINST ESCHERICHIA COLI IN URINARY TRACT INFECTIONS (The Research of Medical Science Review, 2024)
Background: Although majority of the UTIs in adults are uncomplicated infections and are treated with antibiotic empirically, but it is still a major issue for the health system due to antibiotic resistance. Objective: To determine in vitro comparative efficacy of ciprofloxacin and co-trimoxazole against Escherichia coli individuals with UTI Methodology: This Randomized controlled trial was carried out in the Dept. of medicine, Saidu Group of Teaching Hospital (SGTH), Saidu Medical College (SMC) Saidu Sharif Swat, Pakistan from July 01, 2022 – December 31, 2022. Two groups of 97 individuals each were randomly selected from a total of 194 patients who had been diagnosed with an E. Coli urinary tract infection. Following the 48th hour of therapy, all of the enrolled patients were monitored, and the outcomes were documented. SPSS version 24 was used to analyze all of the data. Results: Participants in group A had an average age of 48.4 + 11.1 years, whereas those in group B had an average age of 48.2 + 11.5 years (p value 0.913). Group B had 80.4% males and 19.6% females, whereas group A had 69.1% males and 30.9% females (p value 0.069). Groups A and B had effectiveness rates of 79.3% and 50.5%, correspondingly, after 48 hours after end therapy (p value 0.000). Conclusion: Our research work concludes that ciprofloxacin is more effective than co-trimoxazole in the treatment of UTIs due to E.Coli. Although, literature suggested growing resistance of E Coli to commonly used antibiotics, we would recommend in vitro studies for antibiotic sensitivity testing before making future recommendations.